The mRNA vaccine, a swift warhead against a moving infectious disease target - Sheema Mir; Mohammad Mir (Taylor & Francis Group, 2024)
ABSTRACTIntroduction The rapid development of mRNA vaccines against SARS-CoV-2 has revolutionized vaccinology, offering hope for swift responses to emerging infectious diseases. Initially met with skepticism, mRNA vaccines have proven effective and safe, reducing vaccine hesitancy amid the evolving COVID-19 pandemic. The COVID-19 pandemic has demonstrated that the time required to modify mRNA vaccines to counter new mutant strains is significantly shorter than the time it takes for pathogens to mutate and generate new variants that can thrive in vaccinated populations. This highlights the notion that mRNA vaccine technology appears to be outpacing viruses in the ongoing evolutionary race.Areas covered This review article offers valuable insights into several crucial aspects of mRNA vaccine development and deployment, including the fundamentals of mRNA vaccine design and synthesis, the utilization of delivery systems, considerations regarding vaccine safety, the longevity of the immune response, strategies for modifying the original mRNA vaccine to address emerging mutant strains, as well as addressing vaccine hesitancy and potential approaches to mitigate reluctance.Expert opinion Challenges such as stability, storage, manufacturing complexities, production capacity, allergic reactions, long-term effects, accessibility, and misinformation must be addressed. Despite these hurdles, mRNA vaccine technology holds promise for revolutionizing future vaccination strategies.